2017
DOI: 10.1186/s13013-017-0146-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional digital photography for child body posture evaluation: standardized technique, reliable parameters and normative data for age 7-10 years

Abstract: BackgroundDigital photogrammetry provides measurements of body angles or distances which allow for quantitative posture assessment with or without the use of external markers. It is becoming an increasingly popular tool for the assessment of the musculoskeletal system. The aim of this paper is to present a structured method for the analysis of posture and its changes using a standardized digital photography technique.Material and methodsThe purpose of the study was twofold. The first one comprised 91 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 119 publications
1
40
0
Order By: Relevance
“…After 60 s, a third posture photo was taken. The following posture parameters were determined by means of the Corpus Concepts posture analysis software (AFG, Idar-Oberstein, Germany) for each posture state: posture index, upper body tilt, trunk tilt ( Krawczky et al., 2014 ; Ludwig et al., 2016a ; Stolinski et al., 2017 ). Figure 3 explains these posture parameters.…”
Section: Methodsmentioning
confidence: 99%
“…After 60 s, a third posture photo was taken. The following posture parameters were determined by means of the Corpus Concepts posture analysis software (AFG, Idar-Oberstein, Germany) for each posture state: posture index, upper body tilt, trunk tilt ( Krawczky et al., 2014 ; Ludwig et al., 2016a ; Stolinski et al., 2017 ). Figure 3 explains these posture parameters.…”
Section: Methodsmentioning
confidence: 99%
“…It is a trustworthy and easy-to-use instrument for researchers and clinicians that also contributes to the reduction of patient exposure to ionizing radiation. 19,20 In photogrammetry, some efforts have been made to improve this instrument, like standardization of procedures for data collection and processing of results. However, to the best of our knowledge there is no software capable of measuring the spinal inclination angle similarly to the Cobb angle.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…However, to the best of our knowledge there is no software capable of measuring the spinal inclination angle similarly to the Cobb angle. 19 Using photogrammetry, de Souza et al 21 identified scoliosis in 68% of their evaluated participants. However, the concurrent validity and accuracy of the protocol and software used do not assure the trustworthiness of their results in comparison to the gold standard, the radiographic examination.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…It is stated that posture screening mobile program can be used safely in posture analysis and head position can be evaluated with this technology (Boland Neufeld, Ruddell, Dolezal, & Cooper, 2016). Stolinski et al (2017) have demonstrated the reliability of photographic measurements by comparing the conventional posture measurement methods used with measurements done on photographs. The study to demonstrate the reliability and validity of mobile applications in postural analysis has proven their usefulness in clinical and field surveys (Szucs & Brown, 2018).…”
Section: Discussionmentioning
confidence: 99%